Book Review Podcasting in the Implementation of Extensive Reading: Exploring the Students’ Benefits - Atta Rilysia Azis; Evi Puspitasari (Universitas Muhammadiyah Yogyakarta, 2019)
Book review podcasting is one of the alternatives follow up activities in extensive reading. This type of activity is a result of integrating book review, a common post-reading assignment, and podcasting, a digital recording in a share-comment internet platform. This research aims to discuss the benefits that the students get from the activity in the implementation of extensive reading. This research belongs to qualitative research and took place in one English language education department of a university in Indonesia. The researchers collected the data by interviewing four first-year students who joined a reading-writing class where the lecturer implemented extensive reading. To gain answers from different perspectives, the researchers involved two participants with high reading interest and two others with low interest in that activity. Those four participants who were all female were chosen based on the recommendation from the lecturer. The result pointed out that book review podcasting could enhance students’ reading interest, improve language skills, get a recommendation of good books from friends, and get parents’ support to cultivate reading habits. The conclusion drawn from the finding is that creating a book review podcast as the follow-up activity after the extensive reading has a positive impact on the students.